PHOTOGRAPHY DESIGN OF ZAPIN DANCE CREATIVE DANCE PHOTOGRAPHY WITH QUALITATIVE ANALYSIS IN BATAM CITY - Zulkarnain Zulkarnain; Nowita Wati (Universitas Internasional Batam, 2022)
Photography is a technique of taking photos using a camera. Of course, photography is also well known to the wider community to capture the moment. Fashion is the way people dress according to current trends. Fashion can also be trusted to increase individual confidence. In fashion photography, it is intended to take pictures of the clothes worn by one of the dancers. The dancers referred to in the dance created by Zapin in the city of Batam. This Zapin dance has been passed down to the people of Batam. Zapin dance creations can also be interpreted as a modified zapin dance. In designing fashion photography of dance dancers created by Zapin, the aim is to introduce the clothes worn by one of the dancers in Batam. The clothes worn by the Malay brackets and accessories. The author made with Photoshop CC 2020 and Corel Draw 2019 applications in photo editing. Then the author uses the Multimedia Development Life Cycle (MDLC) method to assist the process of designing a photobook. The author collects data with documentation and interviews. The result of this fashion photography design for dance dancers created by Zapin is a photobook that is printed in the form of a photo book. This photo book contains a collection of photos of dance dancers created by Zapin who wear clothes and accessories in the city of Batam. This photo book is expected to be able to attract local and foreign people in providing information about the dance fashion created by Zapin in Batam.